2006
DOI: 10.1038/sj.emboj.7601030
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic function for the Dlg1 mammalian homolog of the Drosophila discs-large tumor suppressor

Abstract: The fact that several different human virus oncoproteins, including adenovirus type 9 E4-ORF1, evolved to target the Dlg1 mammalian homolog of the membrane-associated Drosophila discs-large tumor suppressor has implicated this cellular factor in human cancer. Despite a general belief that such interactions function solely to inactivate this suspected human tumor suppressor protein, we demonstrate here that E4-ORF1 specifically requires endogenous Dlg1 to provoke oncogenic activation of phosphatidylinositol 3-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(117 citation statements)
references
References 56 publications
(85 reference statements)
6
110
0
Order By: Relevance
“…Ras is an important mediator of anti-apoptotic signals induced by survival factors and promotes survival of many cell systems by activating the PI 3-kinase/PKB pathway (26,27). Role of Ras in increased glucose uptake has been previously reported (28), and other adenoviruses have been reported to activate Ras or PI 3-kinase (18,29,30). However, effect of these adenoviruses on glucose uptake by HSKM cells is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ras is an important mediator of anti-apoptotic signals induced by survival factors and promotes survival of many cell systems by activating the PI 3-kinase/PKB pathway (26,27). Role of Ras in increased glucose uptake has been previously reported (28), and other adenoviruses have been reported to activate Ras or PI 3-kinase (18,29,30). However, effect of these adenoviruses on glucose uptake by HSKM cells is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Ad-36 infection increased Ras protein abundance in HSKM cells. Ras signaling activates PI 3-kinase (17), which is also a pathway used by human adenovirus type 9 for PI 3-kinase activation (18). Therefore, Ras signaling was a candidate pathway for activation of PI 3-kinase by Ad-36.…”
Section: Diabetes Vol 57 July 2008mentioning
confidence: 99%
“…For instance, E4 orf-1 of Ad-9, another human adenovirus that shares subgroup D with Ad-36, activates PI3K via its PDZ domain-binding region by interacting with cellular protein Dlg1 in mouse embryo fibroblasts. 18,31 Ad-9 significantly increases lipid accumulation in 3T3-L1 cells 32 and its E4 orf-1 gene shares 92% homology with amino-acid sequence of Ad-36 E4 orf1, but its in vivo adipogenic effect is unknown. Ad-19, Ad-5 vector induce PI3K pathway 33,34 but their adipogenic genes are not yet identified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MAPK, the other conserved key mediators of Ras action, Ral and PI3K signalling, need to be considered. With regard to PI3K, it is of interest that the constitutive activation of PI3K by the adenovirus 9 E4ORF1 oncoprotein appears to be Dlg1-dependent (Frese et al, 2006) and that Dlg1 itself has been shown to be able to bind to PTEN, a negative regulator of the PI3K pathway (Adey et al, 2000). Furthermore, it remains to be established whether Dlg and Lgl can also regulate Ras signalling, and what the functional significance of the regulation of PI3K and JNK by Scribble/Dlg/Lgl may be in tumour development.…”
Section: Scribble/dlg/lgl and Other Polarity Complexesmentioning
confidence: 99%
“…Indeed, Dlg1 is the only PDZ-containing substrate common to the oncogenic determinants of HPV, human adenovirus 9 and HTLV-1 (human T-cell lymphotropic virus; Lee et al, 1997). It is also notable that Dlg1 binds to two classic tumour suppressors, adenomatous polyposis coli (APC) (a negative regulator of the Wnt pathway) and PTEN (a negative regulator of the PI3K pathway), and is also associated with two protooncogenes, PI3K and Net1 (see further below) (Matsumine et al, 1996;Valiente et al, 2005;Frese et al, 2006;Garcia-Mata et al, 2007). Multiple studies have investigated the association of Dlg1 with HPV-induced gynaecological malignancies (Watson et al, 2002;Cavatorta et al, 2004;Lin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%